The Role of Defensins in HIV Pathogenesis - Barcley T. Pace; Andrew A. Lackner; Edith Porter; Bapi Pahar (Mediators of Inflammation)
Profound loss of CD4+ T cells, progressive impairment of the immune system, inflammation, and sustained immune activation are the characteristics of human immunodeficiency virus-1 (HIV-1) infection. Innate immune responses respond immediately from the day of HIV infection, and a thorough understanding of the interaction between several innate immune cells and HIV-1 is essential to determine to what extent those cells play a crucial role in controlling HIV-1 in vivo. Defensins, divided into the three subfamilies α-, β-, and θ-defensins based on structure and disulfide linkages, comprise a critical component of the innate immune response and exhibit anti-HIV-1 activities and immunomodulatory capabilities. In humans, only α- and β-defensins are expressed in various tissues and have broad impacts on HIV-1 transmission, replication, and disease progression. θ-defensins have been identified as functional peptides in Old World monkeys, but not in humans. Instead, θ-defensins exist only as pseudogenes in humans, chimpanzees, and gorillas. The use of the synthetic θ-defensin peptide “retrocyclin” as an antiviral therapy was shown to be promising, and further research into the development of defensin-based HIV-1 therapeutics is needed. This review focuses on the role of defensins in HIV-1 pathogenesis and highlights future research efforts that warrant investigation.